A system test platform for the CERN power converter control electronics. (1st May 2022) - Cabrera, G.; Grimmer, R.; Haynes, P.; Nisbet, D.
Abstract: The power converters at CERN deliver a broad range of complex functions to assure the correct magnetic field throughout the beam acceleration cycle. The power converter controls are composed of remotely programmable electronics to handle the different characteristics of these power systems, that can supply up to 10 MW, 100 kV and 100 kA. However, such flexibility in the control devices is vulnerable to regression. Avoiding it before the deployment of new or modified software or firmware was the objective for the development of the test platform presented in this paper. It is important to detect possible incompatibilities between versions or errors that could damage the power converters. To achieve this, the platform uses continuous integration and continuous delivery techniques and hardware-in-the-loop modelling to emulate the different power converters range and to validate the controls before deployment.